Analisis User Experience pada Aplikasi M-Banking Bank DKI Menggunakan Metode UEQ - Hany Maria Valentine; Lira Arum Kusumaning Thyas; Ahmad Sandy Maulana (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Researchers made observations of user reviews who complained about problems such as bugs, unstable performance, and errors when purchasing. This study aims to analyze the User Experience (UX) on the JakOne Mobile application. The methods used include literature study, data collection and processing through the UEQ questionnaire, as well as analysis and discussion of the results. The results of the analysis show that of the six UEQ rating scales, five scales (Attractiveness, Clarity, Efficiency, Stimulation, and Novelty) get Excellent scores, while the Accuracy scale gets Bad scores. In UX analysis, the JakOne Mobile application has a very good benchmark level with 10% the best result and 25% the worst result. The assessment aspects of Attractiveness, Perspicuity, Efficiency, Stimulation, and Novelty are in the positive zone, while Dependability is in the negative zone. The results showed that the JakOne Mobile application received good marks from users, especially at Gunadarma University, the Information Systems Department class of 2020. This research provides input for Bank DKI and application developers to improve service quality to users. Thus, this research contributes to understanding the user experience and improving the JakOne Mobile application.